Performance Structural Analysis of U2C Building with the Kobe Earthquake Spectrum - Andi Yusra; Andi Mustafa; Meidia Refiyanni; Zakia Zakia (International Journal of Engineering, Science and Information Technology, 2023)
An investigation into the performance of the building structure in receiving the earthquake load must ensure that the building structure is able to receive it within safe limits. A non-linear approach is generally done through pushover analysis. The purpose of this study is to find out how the behavior or performance of building structures when receiving earthquake loads. The analysis is carried out by modeling the structure of the building using the help of the STERA 3D application. Then it is done by entering the Kobe earthquake spectrum data into the software. From the results of the analysis, the value of the deviation between directional levels X 0.0058 m with a base shear of 10,090 KN was obtained. While the Y direction capacity curve has the largest displacement of 0.0084 m with a base shear of 13,270 KN. The result of structural deviation when the performance point is reached for X direction and Y direction loading of 0.0042 m and 0.0063 m, resulting in a yellow color at each point of the column and beam relationship which means that it is still within the range of 1 U 5 (AMP (response force) analysis), this indicates that the condition of the building structure remains safe during an earthquake.